Bioaccessibility and HPLC-MS/MS chemical characterization of phenolic antioxidants in Red Chicory (Cichorium intybus). (June 2017) - Bergantin, Caterina; Maietti, Annalisa; Cavazzini, Alberto; Pasti, Luisa; Tedeschi, Paola; Brandolini, Vincenzo; Marchetti, Nicola
Highlights: Partial chemical characterization of two cultivars of red chicory was obtained. Structural identification of target bioactives was achieved by HPLC-MS/MS. Bioaccessibility of polyphenols was obtained by in-vitro static simulated digestion. Structure-bioaccessibility relationships were evidenced for target polyphenols. Abstract: Two varieties of red chicory from southern Po Delta area have been characterized in terms of polyphenols content by HPLC-MS/MS. Seven target compounds were selected for determining their bioaccessibility from vegetable matrix. Simulated digestion process was employed for this purpose by means of an in-vitro static model. Salivary, gastric and duodenal phases were realized by using solutions of different physiological enzymes miming the stages of digestion process. Results show well defined behaviors associated with specific structures of aglycone or phenolic acid and position of O-glycosyl moiety. Dicaffeoyltartaric acid together with apigenin-7-O-glucoside and kaempferol-7-O-glucoside have similar bioaccessibility trend that is characterized by a higher value for duodenal phase than for gastric one. Quercetin-3-O-(6″-O-malonyl)-glucoside behaves in reverse way and gastric bioaccessibility turns higher than duodenal. Lastly, the difference between gastric and duodenal bioaccessibility is enhanced in the case of cyanidin-3-O-glucoside and the isomers of caffeoylquinic acid.